2021
DOI: 10.1002/jor.25208
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic effects and arthritic changes following tramadol administration in a rat hip osteoarthritis model

Abstract: We investigated the analgesic effects of tramadol and the arthritic changes following tramadol administration in the rat hip osteoarthritis (OA) model using mono‐iodoacetate (MIA). The right hip joints of male Sprague–Dawley rats (n = 5 rats/group) in the Sham group were injected with 25 μl of sterile saline and 1% of fluorogold (FG) retrograde neurotracer. In the MIA + Vehicle and MIA + Tramadol groups, FG and 25 μl of sterile saline with 0.5 mg of MIA were injected into the right hip joint. The MIA + Vehicle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 47 publications
0
3
1
Order By: Relevance
“…Pathologically and radiographically, DF-HA was ineffective in improving or inhibiting the progression of joint deformity; in contrast, there was no progression of deformity due to excessive analgesia. As Kanno et al [26] reported, drugs with strong analgesic effects such as tramadol risk worsening arthropathy, but the results of this study showed that DF-HA reduced pain but did not worsen arthropathy. This may be because HA has a protective effect on joints and promotes the synthesis of proteoglycans and glycosaminoglycans [43].…”
Section: Discussioncontrasting
confidence: 59%
See 2 more Smart Citations
“…Pathologically and radiographically, DF-HA was ineffective in improving or inhibiting the progression of joint deformity; in contrast, there was no progression of deformity due to excessive analgesia. As Kanno et al [26] reported, drugs with strong analgesic effects such as tramadol risk worsening arthropathy, but the results of this study showed that DF-HA reduced pain but did not worsen arthropathy. This may be because HA has a protective effect on joints and promotes the synthesis of proteoglycans and glycosaminoglycans [43].…”
Section: Discussioncontrasting
confidence: 59%
“…However, DF-HA may exert better analgesic and jointprotective effects in patients with mild OA. Yoh et al [29] reported that 0.25 mg or 0.5 mg MIA intra-articular injection to hip in rats induced mild OA this year, moreover, Kanno et al [26] also reported arthropathic changes and pain behavior assessment in a rat model of hip osteoarthritis at 0.5 mg MIA. We believe it is necessary to compare the effects of DF-HA with those of low-dose MIA administration models such as 0.25 mg and 0.5 mg in the future.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that the regeneration ability of cartilage tissue is very limited if it is damaged [25]. In the speci c case of femoral head cartilage, studies have shown that the degradation of femoral head cartilage plays an important role in the etiology of osteonecrosis and osteoarthritis of the femoral head [26][27][28]. Osteoarthritis of the hip joint is a health problem that negatively affects the economy due to the loss of work in the working population and high treatment costs [29].…”
Section: Discussionmentioning
confidence: 99%